Analysis of Current State of SWAT Model Research Based on Bibliometrics - DU Bailin; WU Lei (Renmin Zhujiang)
In order to gain insights into the latest advancements,focal areas,and future directions in SWAT model research,this paper conducted a bibliometric analysis of its applications in eco-hydrological modeling by using the Web of ScienceTM core database and the VOSviewer visualization software.The findings reveal that from 2000 to 2022,there has been a general increase in publications related to the SWAT model.Research efforts have primarily concentrated on three main areas:firstly,the hydrological simulation applications of the SWAT model to enhance scientific water resource management;secondly,investigations into the mechanisms of hydrological responses to climate and human activities,offering theoretical support for flood disaster prediction and response;lastly,studies on water quality simulation and optimal management strategies,providing theoretical foundations for the prevention and control of agricultural non-point source pollution.The distribution of research teams has shifted from concentrated to more dispersed.Future SWAT research will prominently focus on water resource management,hydrological response processes,and water quality simulation.